More than a marker: potential pathogenic functions of MAP2 - DeGiosio, Rebecca A.; Grubisha, Melanie J.; MacDonald, Matthew L.; McKinney, Brandon C.; Camacho, Carlos J.; Sweet, Robert A. (Frontiers in Molecular Neuroscience, 2022)
Microtubule-associated protein 2 (MAP2) is the predominant cytoskeletal regulator within neuronal dendrites, abundant and specific enough to serve as a robust somatodendritic marker. It influences microtubule dynamics and microtubule/actin interactions to control neurite outgrowth and synaptic functions, similarly to the closely related MAP Tau. Though pathology of Tau has been well appreciated in the context of neurodegenerative disorders, the consequences of pathologically dysregulated MAP2 have been little explored, despite alterations in its immunoreactivity, expression, splicing and/or stability being observed in a variety of neurodegenerative and neuropsychiatric disorders including Huntington’s disease, prion disease, schizophrenia, autism, major depression and bipolar disorder. Here we review the understood structure and functions of MAP2, including in neurite outgrowth, synaptic plasticity, and regulation of protein folding/transport. We also describe known and potential mechanisms by which MAP2 can be regulated via post-translational modification. Then, we assess existing evidence of its dysregulation in various brain disorders, including from immunohistochemical and (phospho)proteomic data. We propose pathways by which MAP2 pathology could contribute to endophenotypes which characterize these disorders, giving rise to the concept of a “MAP2opathy” – a series of disorders characterized by alterations in MAP2 function.